Heart rate‐corrected QT interval is a novel risk marker for the progression of albuminuria in people with Type 2 diabetes. Issue 9 (26th February 2015) - Hashimoto, Y.; Tanaka, M.; Senmaru, T.; Okada, H.; Hamaguchi, M.; Asano, M.; Yamazaki, M.; Oda, Y.; Hasegawa, G.; Nakamura, N.; Fukui, M.
Abstract Aims A close association between heart rate‐corrected QT interval (QTc) and albuminuria in people with Type 2 diabetes has been reported in cross sectional studies. The aim of this study was to evaluate the relationship between QTc and change in urine albumin excretion (UAE) or progression of albuminuria in people with Type 2 diabetes. Methods We measured QTc in 251 consecutive people at baseline. We performed a 5‐year follow‐up cohort study to assess the relationship between QTc and change in UAE, defined as an increase of UAE/follow‐up duration (year), or progression of albuminuria, defined as an increase in the category of diabetic nephropathy. Results During follow‐up, 23 of 151 people with normoalbuminuria and 13 of 73 people with microalbuminuria at baseline had progression of albuminuria. Multiple regression analysis demonstrated that QTc was independently associated with change in UAE (β = 0.176, P = 0.0104). Logistic regression analyses showed that QTc was a risk marker for progression of albuminuria [odds ratio per 0.01‐s increase in QTc 1.35, 95% confidence interval (CI) 1.11–1.66, P = 0.0024] after adjusting for confounders. According to the receiver operator characteristic (ROC) analysis, the optimal cut‐off point of QTc for progression of albuminuria was 0.418 s [area under the ROC curve 0.75 (95% CI 0.66–0.82), sensitivity = 0.86, specificity = 0.56, P < 0.0001]. Conclusions Heart rate‐corrected QT interval could be a novel risk marker for progression of albuminuria in people with Type 2 diabetes.